Publishing activity of the permanent commission on organizing people's readings. «Book History» by I. P. Khrushchov - N. G. Kuzmina (Библиосфера)
The article reflects the repertoire of publications in Russian, published in St. Petersburg and intended for public readings in public auditorium. Detailed description of the literature on the history of Russia, in particular, on book history is given. The author considers structure and content of a lecture, details of material presentation, the presence of illustrations and drawings, explaining a text.